Lynching in North Carolina: a history, 1865 - 1941 - Newkirk, Vann R. (McFarland & Company, Inc., Publishers)
Introduction: a place in lynching lore -- Lynching the Carolina way -- Norlina -- The lynching of Plummer Bullock -- A well-deserved punishment -- Canada, o Canada -- The old north state -- One million Klansmen -- Law and order must prevail: North Carolina efforts to punish lynch mob members 1919-1923 -- The Needleman case -- "You don't know what the law will do to you?" A move toward legal lynching -- Lynching in North Carolina 1930-1935 -- A matter for the judiciary -- Summary -- Appendix I. Other notable lynchings -- Appendix II. North Carolina lynchings, 1865-1941 -- Notes -- Bibliography -- Index